2022
DOI: 10.1186/s12888-022-03804-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and substance use disorders: a review of international guidelines for frontline healthcare workers of addiction services

Abstract: Background People with substance use disorders may be at a greater risk of contracting COVID-19 infection and developing medical complications. Several institutional and governmental health agencies across the world developed ad hoc guidance for substance use disorder services and care of individuals misusing substances. We aimed to synthesise the best available recommendations on management and care of people with or at risk of substance use disorders during the COVID-19 pandemic from existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In terms of other practice implications, several of our participants’ strategies align with recommendations for providing services to substance-using populations during the COVID-19 pandemic that were identified in a recent review [ 60 ]. For example, the common strategy of staying connected to maintain one’s recovery is reflected in recommendations to “create a buddy and self-support system with someone trusted and to reach out for extra help if needed.” In addition, several other qualitative themes emerging from this study are reflected in recent recommendations for services to substance-using populations (e.g., maintaining normalcy and a routine; drawing upon general social support and peers in recovery; using mutual-help groups).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of other practice implications, several of our participants’ strategies align with recommendations for providing services to substance-using populations during the COVID-19 pandemic that were identified in a recent review [ 60 ]. For example, the common strategy of staying connected to maintain one’s recovery is reflected in recommendations to “create a buddy and self-support system with someone trusted and to reach out for extra help if needed.” In addition, several other qualitative themes emerging from this study are reflected in recent recommendations for services to substance-using populations (e.g., maintaining normalcy and a routine; drawing upon general social support and peers in recovery; using mutual-help groups).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is critical to educate society about the consequences of unauthorized opium consumption. Ostinelli et al synthesized the best available recommendations on the management and care of individuals at risk of substance use disorders during the COVID-19 pandemic and observed that current guidance does not provide advice on service access strategies tailored to individuals with substance use disorders [53].…”
Section: Discussionmentioning
confidence: 99%
“…Initially we focused on immediate priority areas. The rapid transition to telepsychiatry services [ 17 , 18 ] prompted the need for guidance syntheses regarding digital approaches and telepsychiatry [ 19 ], followed by other areas of mental health including inpatient care; use of clozapine, lithium, and antipsychotics; suicide and self-harm; domestic violence and abuse; substance use disorders [ 20 ]; perinatal care [ 21 ]; and vaccine prioritization [ 22 ] and hesitancy [ 23 ] in the context of mental illness. The team updated the guidance regularly and collaborated with experts in each area to keep the guidance focused, comprehensive, and globally representative.…”
Section: Methodsmentioning
confidence: 99%